2007
DOI: 10.1371/journal.pmed.0040018
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic Profiling of the Amniotic Fluid to Detect Inflammation, Infection, and Neonatal Sepsis

Abstract: BackgroundProteomic analysis of amniotic fluid shows the presence of biomarkers characteristic of intrauterine inflammation. We sought to validate prospectively the clinical utility of one such proteomic profile, the Mass Restricted (MR) score.Methods and FindingsWe enrolled 169 consecutive women with singleton pregnancies admitted with preterm labor or preterm premature rupture of membranes. All women had a clinically indicated amniocentesis to rule out intra-amniotic infection. A proteomic fingerprint (MR sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
159
3

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 157 publications
(168 citation statements)
references
References 35 publications
6
159
3
Order By: Relevance
“…Our results are slightly different from the previous reports, which communicate that the sTLR2 system is comprised of six polypeptides (83, 66, 50, 40, 38 and 25 kDa) in human breast milk and plasma (15), and three polypeptides (55,40, and 27 kDA) in the human parotid saliva (14). In our study we showed that the 98-kDa polypeptide corresponds to the full-length transmembrane TLR2 by using as control placental villous tissue, which lacks the two amniotic fluid isoforms attributable to sTLR2.…”
Section: Discussioncontrasting
confidence: 99%
“…Our results are slightly different from the previous reports, which communicate that the sTLR2 system is comprised of six polypeptides (83, 66, 50, 40, 38 and 25 kDa) in human breast milk and plasma (15), and three polypeptides (55,40, and 27 kDA) in the human parotid saliva (14). In our study we showed that the 98-kDa polypeptide corresponds to the full-length transmembrane TLR2 by using as control placental villous tissue, which lacks the two amniotic fluid isoforms attributable to sTLR2.…”
Section: Discussioncontrasting
confidence: 99%
“…In conclusion, our studies of placentas from congenital infection and primary cells isolated from various donors and placentas from mid-gestation and late gestation suggest that persistent HCMV infection in fetal membranes could promote inflammation 20,21 and contribute to preterm labor and delivery. 27 Understanding the basis for persistent infection in AmEpCs could lead to therapeutic strategies to prevent congenital disease and pregnancy complications by targeting viral functions that promote persistence and enhancing host antiviral responses that suppress infection.…”
Section: Hcmv Persistent Hcmv Infection In the Amnionmentioning
confidence: 75%
“…[32] In an effort to avoid unnecessary antibiotic administration, attention has turned toward new diagnostic approaches such as the description of biomarkers and hematological indices designed to identify neonates at risk for sepsis and poor outcome. [21,28,30] The importance of this concept is predicated by studies which demonstrate that general hematological indices and NRBCs are good predictors of short term neonatal outcome, independent of gestational age or birth weight. [4,33,34] This suggests that at birth, description of hematological indices and serologic markers even in the absence of positive cultures carries not only diagnostic and prognostic value, but also provides insight into the pathophysiology of fetal adaptation to a microbial inflammatory attack.…”
Section: Discussionmentioning
confidence: 99%
“…[21] Briefly, the amniotic fluid proteomic fingerprint, the Mass Restricted (MR) score, was generated immediately following the retrieval of amniotic fluid. The MR score provides qualitative information regarding the presence or absence of inflammation.…”
Section: Diagnosis Of Intra-amniotic Inflammationmentioning
confidence: 99%